Influence of curing conditions on the morphologies of a PMMA-modified epoxy matrix - Remiro, P.M. (2001)
The effect of curing conditions such as time and temperature on the morphology developed in a diglycidyl ether of bisphenol-A epoxy resin cured with diamino diphenyl methane, and modified with 15 wt% poly(methyl methacrylate), has been investigated. The reacting mixtures were precured at 80°C for a period of time ranging from 2 to 7 h, afterwards they were cured at 140°C and finally postcured at 200°C. The mixtures were opaque or transparent depending on the precuring time. Dynamic mechanical thermal analysis suggested that all mixtures were heterogeneous. However, phase separation occurred for all precuring times but to a lesser extent for samples precured for 5, 6 or 7 h than for those precured for shorter time intervals at 80°C. Two phases were clearly distinguished by atomic force microscopy, in all mixtures. The phase size was controlled, on one hand, by the time the phases had to grow, i.e. the interval between the cloud and gel points, and on the other hand, by the viscosity of the reacting mixture at the moment of phase separation.